SISTEM INFORMASI E-CATERING BERBASIS WEB PADA RUMAH MAKAN PONDOK BAMBU BULUKUMBA - Laela, Nur; Farida, Farida; Syam, Nurwahid (CV. LAJAGOE PUSTAKA, 2024)
Study this aim for : (1) designing and build System Information E-Catering Web Based On House Eat Cottage Bambu Bulukumba (2) know effectiveness web -based catering orders on House Eat Cottage Bambu Bulukumba. Study this use method Research and development (R&D) is something process or steps for develop something product new or perfect products that have been there is . Method this have stages namely : potential and problem , collect information , design product , validation design , repair design , test try product , revision product , test try usage , revision product , manufacture product bulk . Results from study this are : (1) System information e-catering web based on House Eat Cottage Bambu Bulukumba ,designed use software visual studio code (text editor) , language programming used PHP, database management system (DBMS) Mysql as storage database , method used _ is Research and Development ( R&D ) methods which includes potency problem, collect information ,design product ,validation design ,repair design ,test try product ,revision product ,test try usage,revision product continue ,and making product bulk. As well as the tests carried out with use methodblackbox testing .(2) Testing use method System Usability Scale SUS with the value obtained is 76.4 which means grade scale B or same withcategory Good which means System Information E-Catering Web Based On House Eat Cottage Bambu Bulukumba this effective used in booking catering packages and could used with easy by users .